Monadic Decomposition - Veanes, Margus; Bjørner, Nikolaj; Nachmanson, Lev; Bereg, Sergey (CAV'14, 2014)
Monadic predicates play a prominent role in many decidable cases, including decision procedures for symbolic automata. We are here interested in discovering whether a formula can be rewritten into a Boolean combination of monadic predicates. Our setting is quantifier-free formulas over a decidable background theory, such as arithmetic and we here develop a semi-decision procedure for extracting a monadic decomposition of a formula when it exists.